PENGARUH IMPLEMENTASI MODUL AJAR MAKANAN DAN SISTEM PENCERNAAN TERHADAP PENGETAHUAN DAN SIKAP PENCEGAHAN DINI STUNTING SISWA SMA NEGERI 1 TAKALAR - Zulfikar, Muhammad Anjas; Azis, A. Asmawati; Taiyeb, A. Mushawwir (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study aims to investigate the effect of implementing a teaching module on food and the digestive system on students’ knowledge and attitudes regarding the early prevention of stunting at SMA Negeri 1 Takalar. This research employed a pre-experimental design. The population consisted of 212 eleventh-grade students who had chosen biology. Using random sampling, classes XI F3 and XI F4 were selected as the sample, comprising a total of 72 students. Respondents were given a pretest, followed by a learning session using the teaching module, and then a posttest. The data were analyzed using descriptive statistics and inferential analysis through a paired sample t-test. The descriptive analysis revealed that, in the pretest, most students demonstrated very poor knowledge and negative attitudes. In contrast, posttest results showed that the majority had very good knowledge and positive attitudes. The inferential analysis indicated a significant effect of the teaching module on both knowledge and attitudes regarding the early prevention of stunting, with a significance value of 0.000 < 0.05 for both aspects.